Preparation method of sapphire optical fiber double cladding with high temperature resistance and long-term service in air

By preparing the BN/SiC double cladding on the surface of sapphire optical fiber, the problems of insufficient transmission loss and mechanical performance in high-temperature environments are solved, and long-term service capability and high-efficiency optical transmission are achieved in an air environment of 1500℃.

CN119736606AActive Publication Date: 2025-04-01NORTHWESTERN POLYTECHNICAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411666797.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-04-01
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing sapphire optical fibers have high transmission losses and insufficient mechanical properties in high temperature environments, and the cladding cannot be used stably in an air environment of 1500℃, and the long-term service capacity is insufficient.

Method used

Using a double cladding design, the inner cladding is BN and the outer cladding is SiC. A dense and continuous BN/SiC double cladding is prepared on the surface of sapphire optical fiber by chemical vapor deposition to improve its mechanical and optical properties at high temperatures.

Benefits of technology

The intensity and mechanical properties of sapphire fiber in an air environment of 1500℃ are significantly improved, the optical transmission loss is reduced, and the service time at high temperatures is extended. SiC of suitable thickness can make sapphire fiber/BN/SiC in an air environment for at least 150 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736606A_ABST
    Figure CN119736606A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a sapphire optical fiber double-cladding layer capable of resisting high temperature and serving for a long time in air. A compact and continuous BN / SiC double-cladding layer is prepared on the surface of a sapphire optical fiber through a chemical vapor deposition method. The refractive index of the sapphire optical fiber / BN / SiC and BN is slightly lower than that of the sapphire optical fiber, the sapphire optical fiber / BN / SiC and BN serve as a total reflection layer of the optical fiber, the slow oxidation rate of SiC at a high temperature can provide durable protection for a BN inner cladding layer, the BN is prepared on the surface of the sapphire optical fiber, defects on the surface of the sapphire optical fiber can be repaired, and on the other hand, the transmission loss of the sapphire optical fiber can be reduced; secondly, the BN / SiC double cladding prepared on the surface of the sapphire optical fiber can improve the mechanical property of the sapphire optical fiber at high temperature, and the linearization of a stress-strain curve of the sapphire optical fiber is enhanced; in addition, the slow oxidation rate of the SiC outer cladding in the 1500 DEG C-air environment enhances the long-term service capacity of the sapphire fiber / BN / SiC in the environment, and the SiC with the appropriate thickness can make the service capacity of the sapphire fiber / BN / SiC in the 1500 DEG C-air environment reach 150 h or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of low-loss and high-temperature-resistant cladding preparation of sapphire optical fibers, and mainly relates to a method for preparing a multilayer ceramic cladding which is high-temperature-resistant and can serve for a long time. Background Art

[0002] In the fields of aviation and aerospace, some structural parts will creep during long-term service. Once the creep of the component reaches the limit, the entire equipment may have catastrophic consequences. Before the component reaches its expected life, timely detection of problems and replacement of damaged components are of positive significance for reducing maintenance costs and improving mission efficiency. Sapphire fiber sensors have the advantages of small size, light weight, high temperature resistance, anti-electromagnetic interference, safety and reliability, and have great potential for component health detection. However, the current sapphire fiber Bragg sensors lack suitable cladding at high temperatures, have high transmission losses at high temperatures (>1200℃), and impurities in the environment are adsorbed on the surface of sapphire fiber, which easily causes light scattering. In addition, the lack of mechanical properties of sapphire fiber at high temperatures restricts its wider application. Therefore, it is necessary to prepare a cladding on the surface of sapphire fiber to improve its mechanical and optical properties at high temperatures.

[0003] At present, the outer cladding of sapphire optical fiber includes high melting point metal, ceramic cladding, etc. The metal cladding includes platinum, niobium, iridium and other elements, and the non-metallic cladding includes BN, SiBCN, SiO 2 、TiO 2 、ZrO 2 MgAl 2 O 4 The metal coating prepared on the optical fiber surface by magnetron sputtering, sol-gel and other processes often faces problems such as oxidation, agglomeration and evaporation at high temperatures, making it difficult to use it for a long time in high temperature and harsh environments. 2 Although the cladding can remain stable in oxidizing and moderately reducing atmospheres, the refractive index of the zirconium oxide cladding is higher than that of sapphire fiber and cannot be used as a total reflection layer. 2 O 3 The cladding can be used at a maximum temperature of 1600°C, but because the cladding and substrate have the same chemical composition, diffusion will occur between the interfaces at high temperatures, and polycrystalline alumina will easily fuse with sapphire, resulting in the disappearance of the core interface between the cladding and the sapphire fiber. 2 O 4 ) has a good thermal expansion coefficient match with sapphire optical fiber, and the cladding used to prepare sapphire optical fiber has interface compatibility. The spinel film still maintains stoichiometry at around 900°C, but as the temperature rises further, the spinel will gradually dissolve Al 2 O 3When the temperature rises to 1400℃, the increase in solubility will promote the diffusion of aluminum from sapphire fiber to MgAl 2 O 4 In the cladding; the long-term stability of spinel film at high temperature restricts its widespread application in sapphire optical fiber cladding.

[0004] In summary, the application temperature conditions of sapphire optical fiber cladding reported in current research are limited, and many material claddings cannot be used stably in an air environment of 1500°C, and their long-term service capabilities are insufficient. Therefore, the present invention aims to achieve long-term service of sapphire optical fiber at high temperatures through a special double cladding design. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, improve the stability in an air environment of 1500°C, and enhance the long-term service capability, the present invention provides a method for preparing a double-cladding sapphire optical fiber capable of high temperature resistance and long-term service in air.

[0006] The present invention aims to improve the ability of sapphire optical fiber to serve for a long time at high temperature through a special double cladding structure design, material selection and preparation method. In the double cladding design, the inner cladding heals the surface defects of the optical fiber and improves its mechanical properties on the one hand, and acts as a total reflection layer to reduce the light transmission loss on the other hand; the outer cladding is used to protect the inner cladding from oxidation due to its high temperature resistance and high chemical stability. Among them, the transmission loss of sapphire fiber / BN / SiC and the residual stress between the interfaces are calculated by COMSOL software to provide a basis for the design of the double cladding structure of sapphire optical fiber, and then a dense and continuous BN / SiC double cladding is prepared on the surface of the sapphire optical fiber by chemical vapor deposition (CVD).

[0007] A method for preparing a double-cladding sapphire optical fiber that is resistant to high temperatures and can be used for a long time in air comprises the following steps:

[0008] Preparation of BN inner cladding:

[0009] Step 1: Clean the sapphire optical fiber and dry it;

[0010] Step 2: Place the dried sapphire optical fiber into the constant temperature zone of the BN deposition furnace;

[0011] Step 3: Reduce the pressure in the BN deposition furnace, introduce argon gas and increase the temperature;

[0012] The pressure in the BN deposition furnace is lower than 3 kPa, argon gas is introduced at the same time, and then the temperature of the BN deposition furnace is raised to 600-1000° C. The argon gas flow rate is 100 ml / min;

[0013] Step 4: introducing gaseous precursor of BN deposition furnace into the BN deposition furnace;

[0014] After the temperature in the BN deposition furnace is stabilized, gaseous precursors are introduced into the BN deposition furnace. The gaseous precursors introduced into the BN deposition furnace include H 2 , Argon, BCl 3 and NH 3 Gas, the gaseous precursor reacts in the reaction chamber of the BN deposition furnace to deposit BN on the surface of the sapphire optical fiber. The BN deposition furnace maintains the temperature for 1-20 hours to obtain a BN inner cladding with a target thickness of 1 to 10 μm;

[0015] Step 5: After the BN inner cladding deposition is completed, cool it to room temperature and place the reacted sapphire optical fiber into a SiC deposition furnace;

[0016] Preparation of SiC outer cladding:

[0017] Step 6: After the temperature in the SiC deposition furnace is raised, a SiC cladding gaseous precursor is introduced;

[0018] The temperature of the SiC deposition furnace is raised to 900-1100°C. After the temperature in the SiC deposition furnace is stabilized, a SiC cladding gaseous precursor is introduced into the SiC deposition furnace. The gaseous precursor in the SiC deposition furnace includes H 2 , argon and MTS; raise the temperature of the methyltrichlorosilane MTS oil bath to 30-35°C, and introduce H into the MTS oil bath by bubbling 2 , pass H 2 Then, the gaseous trichloromethylsilane is taken out to the reaction chamber, and argon gas is introduced into the reaction chamber for dilution, so that the gaseous precursor of the SiC deposition furnace is decomposed, and SiC is generated on the surface of the sapphire optical fiber / BN, and a SiC outer cladding with a target thickness of 1 to 10 μm is obtained;

[0019] Step 7: After the deposition is completed, the introduction of the reaction gas source is stopped, and the deposition furnace is cooled to room temperature to obtain sapphire optical fiber / BN / SiC.

[0020] Furthermore, in step 4, H 2 The flow rate is 50-200ml / min; the BCl 3 The flow rate is 10-100 ml / min; the NH 3 The flow rate is 30-200 ml / min; the argon flow rate is 50-200 ml / min.

[0021] Furthermore, in step 6, H 2 The flow rate is 20-2000 ml / min; the argon flow rate is 10-2000 ml / min.

[0022] Furthermore, in step 6, the temperature is maintained for 1-100 hours.

[0023] The present invention proposes a design and preparation method of a sapphire optical fiber BN / SiC double cladding that can be used for a long time in an air environment at 1500°C. The method has a simple design, a wide operating range, strong substitutability, and good repeatability. Compared with sapphire bare optical fiber, the present invention has the following advantages:

[0024] (1) The BN / SiC double cladding is prepared on the surface of sapphire optical fiber by chemical vapor deposition. The surface is continuous and dense, the interface is well bonded, and it has good structural stability. In the double cladding design, the inner cladding heals the surface defects of the optical fiber and improves its mechanical properties, and on the other hand, it acts as a total reflection layer to reduce light transmission loss. The outer cladding is high temperature resistant and chemically stable to protect the inner cladding from oxidation.

[0025] (2) The strength of sapphire fiber / BN / SiC in 1500℃-air environment is significantly improved while the modulus decreases, and the mechanical properties are significantly improved;

[0026] (3) The BN inner cladding acts as a total reflection layer, which can significantly reduce the transmission loss of sapphire optical fiber;

[0027] (4) The double cladding designed and prepared by the present invention can improve the service capability of sapphire optical fiber at high temperature. The oxide generated by the slow oxidation of the SiC outer cladding at high temperature reduces the air permeation rate, thereby improving the long-term service capability of sapphire optical fiber / BN / SiC. SiC with a suitable thickness can enable the sapphire optical fiber / BN / SiC to serve for at least 150 hours in a 1500°C-air environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 : Some propagation modes of sapphire fiber / BN-5μm / SiC: (a) is Lp01; (b) is Lp02; (c) is Lp21; (d) is Lp31; (e) is Lp41; (f) is Lp22;

[0029] Figure 2 :Changes in transmission loss of some propagation modes of sapphire fiber / BN / SiC under different BN thicknesses;

[0030] Figure 3 :(a) Stress-strain curve of sapphire fiber / BN / SiC in air at 1500℃;(b) Simulation results of radial residual stress of sapphire fiber / BN / SiC at room temperature and 1500℃;

[0031] Figure 4 : Fracture morphology of sapphire fiber / BN-4μm / SiC-6μm at 1500℃: (a) and (b) fracture morphology; (c) and (d) surface morphology;

[0032] Figure 5 :Morphological changes of sapphire fiber / BN-3μm / SiC-20μm before and after oxidation at 1500℃ in air for 8h: (a) before oxidation; (b) after oxidation; DETAILED DESCRIPTION

[0033] A technical solution for preparing a double-cladding sapphire optical fiber that is resistant to high temperatures and can be used for a long time in air is as follows:

[0034] Step 1: Clean the sapphire optical fiber and dry it;

[0035] The sapphire optical fiber is cleaned in an ultrasonic bath using anhydrous ethanol and deionized water in sequence, and the cleaned sapphire optical fiber is placed in an oven to dry;

[0036] Step 2: Place the dried sapphire optical fiber into the constant temperature zone of the BN deposition furnace;

[0037] Place the dried sapphire fiber into a graphite box, fix one end of the sapphire fiber, and leave the other end of the sapphire fiber free, and place the graphite box into the constant temperature zone of the BN deposition furnace;

[0038] Step 3: Reduce the pressure in the BN deposition furnace, introduce argon gas and increase the temperature at the same time.

[0039] The pressure in the BN deposition furnace is pumped down to below 3 kPa, and argon gas is introduced at the same time, and then the temperature of the BN deposition furnace is raised to 600-1000° C. The argon gas flow rate is 100 ml / min;

[0040] Step 4: introducing a gaseous precursor of a BN deposition furnace into the BN deposition furnace;

[0041] After the temperature in the BN deposition furnace is stabilized, gaseous precursors are introduced into the BN deposition furnace. The gaseous precursors in the BN deposition furnace include H 2 , Argon, BCl 3 and NH 3 Gas, the gaseous precursor reacts in the reaction chamber of the BN deposition furnace to deposit BN on the surface of the sapphire optical fiber. The BN deposition furnace maintains the temperature for 1-20 hours to obtain a BN inner cladding with a target thickness of 1 to 10 μm;

[0042] The H 2 The flow rate is 50-200ml / min; the BCl 3 The flow rate is 10-100 ml / min; the NH 3 The flow rate is 30-200 ml / min; the argon flow rate is 50-200 ml / min;

[0043] Step 5: After the BN inner cladding deposition is completed, cool it to room temperature and place the reacted sapphire optical fiber into a SiC deposition furnace;

[0044] After the BN inner cladding deposition is completed, the introduction of the reaction gas source is stopped, and the deposition furnace is cooled to room temperature, and the graphite box is transferred to the SiC deposition furnace;

[0045] Preparation of SiC outer cladding:

[0046] Step 6: introducing SiC cladding gaseous precursor into the SiC deposition furnace;

[0047] The temperature of the SiC deposition furnace is raised to 900-1100°C. After the temperature in the SiC deposition furnace is stabilized, a SiC cladding gaseous precursor is introduced into the SiC deposition furnace. The gaseous precursor in the SiC deposition furnace includes H 2 , argon and MTS; raise the temperature of the methyltrichlorosilane MTS oil bath to 30-35°C, and introduce H into the MTS oil bath by bubbling 2 , pass H 2 Then, the gaseous trichloromethylsilane is taken out to the reaction chamber, and argon gas is introduced into the reaction chamber for dilution, the gaseous precursor of the SiC deposition furnace is decomposed, and SiC is generated on the surface of the sapphire fiber / BN. The temperature is maintained for 1-100 hours to obtain a SiC outer cladding with a target thickness of 1-10 μm; the H 2 The flow rate is 20-2000ml / min; the argon flow rate is 10-2000ml / min;

[0048] Step 7: After the deposition is completed, the introduction of the reaction gas source is stopped, and the deposition furnace is cooled to room temperature to obtain sapphire optical fiber / BN / SiC.

[0049] Example process parameters:

[0050]

[0051]

[0052] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0053] Preparation of BN inner cladding:

[0054] (1) Clean the sapphire optical fiber in an ultrasonic bath with anhydrous ethanol and deionized water, and dry it in an oven;

[0055] (2) Place the dried sapphire fiber in a graphite box and fix one end to ensure that the other end of the sapphire fiber is free, and then place it in the constant temperature zone of the BN deposition furnace;

[0056] (3) The pressure in the BN deposition furnace is pumped down to below 3 kPa, argon gas is introduced at the same time, and then the deposition furnace is heated to 600-1000° C.; the argon gas flow rate is 100 ml / min;

[0057] (4) After the temperature stabilizes, introduce H2, Ar, BCl3, NH3 and other gases, and the gaseous precursors react in the reaction chamber of the deposition furnace to deposit BN on the surface of the sapphire optical fiber. Maintain the temperature for 1-20 hours to obtain BN with a target thickness. The H2 flow rate is 50-200 ml / min; the BCl3 flow rate is 10-100 ml / min; the NH3 flow rate is 30-200 ml / min; and the Ar flow rate is 50-200 ml / min.

[0058] (5) After the deposition is completed, the introduction of the reaction gas source is stopped, and the deposition furnace is cooled to room temperature, and the graphite box is transferred to the SiC deposition furnace.

[0059] Preparation of SiC outer cladding:

[0060] (6) The SiC deposition furnace is raised to 900-1100°C, and the temperature of the methyltrichlorosilane (MTS) oil bath is raised to 30-35°C. Then, H2 is introduced into the MTS oil bath by bubbling to bring out some gaseous trichloromethylsilane into the reaction chamber, and Ar is introduced to dilute it. The gaseous precursor is decomposed to generate SiC on the surface of the sapphire fiber / BN. The temperature is maintained for 1-100 hours to obtain SiC of the target thickness. The H2 flow rate is 20-2000ml / min; the Ar flow rate is 10-2000ml / min.

[0061] (7) After the deposition is completed, the introduction of the reaction gas source is stopped, and the deposition furnace is cooled to room temperature to obtain sapphire optical fiber / BN / SiC.

[0062] Preparation of SiC outer cladding:

[0063] The gas flow rate and deposition temperature required for the BN and SiC deposition processes are not limited to the above ranges, and are dynamically related to the size specifications of the deposition furnace.

[0064] The gas sources for BN deposition process include but are not limited to: H2, Ar, BCl3, NH3; the gas sources for SiC deposition process include but are not limited to: H2, Ar, MTS.

[0065] In order to better illustrate the advantages of the present invention, the present invention is further described below in conjunction with examples and drawings.

[0066] The sapphire fiber / BN / SiC transmission model was simulated by COMSOL, and the results are as follows Figure 1 As shown in Figure 1, the transmitted light is almost entirely confined in the core of the sapphire fiber / BN / SiC. In addition, the propagation loss (leakage loss) corresponding to each propagation mode varies with the BN thickness as shown in Figure 1. Figure 2As shown, it can be seen that with the increase of BN thickness, the transmission loss corresponding to each mode continues to decrease. When the thickness is higher than 3μm, the loss is negligible.

[0067] The mechanical properties test results of sapphire fiber / BN / SiC in 1500℃-air environment are shown in Table 1. The strength of the sample is 648MPa, which is 28% higher than that of the original sapphire fiber; and the elastic modulus is 245GPa, which is 23% lower than that of the original sapphire fiber. The strength of sapphire fiber / BN / SiC is increased and the flexibility is enhanced. The stress-strain curve of the sample at high temperature is shown in Figure 3 As shown in (a), compared with the original sapphire fiber, the stress-strain curve of sapphire fiber / BN / SiC has little fluctuation and remains highly linear. The residual stress in the radial direction of the sapphire fiber / BN / SiC sample at room temperature and high temperature is shown in Figure 3 As shown in (b), since the thermal expansion coefficient and Poisson's ratio of sapphire fiber and SiC are very close, the radial residual stress between the sample interfaces is limited at both room temperature and high temperature, and the cracking tendency between the cladding interfaces is limited. The sapphire fiber / BN / SiC has structural stability.

[0068] The fracture morphology of the sapphire fiber / BN-4μm / SiC-6μm high temperature tensile specimen is as follows Figure 4 As shown in the figure, the fracture surface of the sample is divided into a smooth fracture mirror and a relatively rough, jagged, diamond-shaped dissociation surface. Figure 4 (a) and (b) show that the BN in the inner layer of the sample has been oxidized and lost. This is mainly caused by the BN on the fracture surface being exposed to a high-temperature oxidizing environment after the sample is broken. Figure 4 (a), (b) and (c) show that the SiC on the outer layer of the sample is continuously distributed along the circumference and axial direction of the optical fiber, with no obvious signs of cracking. Secondly, there are large hemispherical cauliflower-like morphologies in local areas of the sample surface. These large aggregates are formed by the fusion of a large number of micron-sized polycrystalline SiC. Overall, the SiC cladding is continuous and there are no gaps between the unit cells. Figure 4 (d) is the morphology of the tensile specimen after the cladding falls off at a local location. It can be seen that many wrinkles appear on the surface of the sapphire fiber after stretching.

[0069] The morphology of sapphire fiber / BN-3μm / SiC-20μm after being tested in 1500℃-air environment for 8h is as follows Figure 5 As shown in the figure, it can be found that 1μm oxide is generated on the surface of the sample after 8h of testing, while the BN in the innermost layer of the sample does not undergo any oxidation. It can be inferred that the cladding of the sapphire fiber / BN / SiC prepared by chemical vapor deposition is continuous and dense and will not crack at room temperature and high temperature, and has the expected structural stability, which is consistent with Figure 3 (d) The residual stress calculation results are consistent. In addition, according to Figure 5 It is known that it takes 8 hours for the SiC outer layer to oxidize 1μm, and the oxides generated on the surface will reduce the air penetration rate. Therefore, based on this oxidation rate, it can be estimated that the sample can be used in a 1500℃-air environment for at least 150 hours.

[0070] High temperature mechanical properties of sapphire fiber / BN / SiC:

[0071] In this paper, sapphire fiber / BN / SiC was prepared and its mechanical properties at high temperature (1500℃) were tested. The results are shown in Table 1. The strength of the sample is 648MPa, which is 28% higher than that of the original sapphire fiber; and the elastic modulus is 245GPa, which is 23% lower than that of the original sapphire fiber. The stress-strain curve of the sample at high temperature is shown in Table 1. Figure 3 As shown in (a), it can be seen that the stress-strain curve fluctuates very little and remains highly linear. The residual stress between the radial directions of the sapphire fiber / BN / SiC samples at room temperature and high temperature is shown in Figure 3 As shown in (b), since the thermal expansion coefficient and Poisson's ratio of sapphire fiber and SiC are very close, the radial residual stress at the sample interface is relatively limited regardless of room temperature or high temperature.

[0072] Table 1 Tensile test results of sapphire fiber / BN-4μm / SiC-6μm at 1500℃

[0073]

[0074] The fracture morphology of the sapphire fiber / BN-4μm / SiC-6μm high temperature sample is as follows Figure 4 As shown. Similar to the fracture of the above sample, the sample fracture surface is divided into a smooth fracture mirror and a relatively rough jagged diamond dissociation surface. The fiber surface on the side of the fracture mirror is the fracture source. During stretching, the crack initiated at the fracture source initially expands at a slower speed. When the crack front is large enough and reaches a higher expansion speed, the crack begins to branch and passes through the remaining part of the fiber section to form a jagged diamond dissociation surface.

[0075] from Figure 4 (a) and (b) show that the BN in the inner layer of the sample has been oxidized and lost, and the SiC in the outer layer of the sample is continuously distributed along the circumference of the fiber without obvious cracking. Figure 4 As shown in (c), there are large hemispherical cauliflower-like morphologies in local areas of the sample surface. These large agglomerates are formed by the fusion of a large number of micron-sized polycrystalline SiC. Overall, the SiC coating is continuous and there are no gaps between the unit cells. Figure 4(d) is the morphology of the tensile specimen after the coating falls off at a local location. It can be seen that many wrinkles appear on the surface of the sapphire optical fiber after stretching. The cause of these wrinkles is the same as the above situation.

Claims

1. A method for preparing a double-cladding sapphire optical fiber that can withstand high temperatures and serve for a long time in air, characterized in that: The steps include: Preparation of BN inner cladding: Step 1: Clean the sapphire optical fiber and dry it; Step 2: Place the dried sapphire optical fiber into the constant temperature zone of the BN deposition furnace; Step 3: Reduce the pressure in the BN deposition furnace, introduce argon gas and increase the temperature; The pressure in the BN deposition furnace is less than 3 kPa, and argon gas is introduced at the same time, and then the BN deposition furnace is heated to 600-1000° C.; the argon gas flow rate is 100 ml / min; Step 4: introducing a gaseous precursor of a BN deposition furnace into the BN deposition furnace; After the temperature in the BN deposition furnace is stabilized, a gaseous precursor is introduced into the BN deposition furnace. The gaseous precursor introduced into the BN deposition furnace includes H2, argon, BCl3 and NH3 gases. The gaseous precursor reacts in the reaction chamber of the BN deposition furnace to deposit BN on the surface of the sapphire optical fiber. The BN deposition furnace maintains the temperature for 1-20 hours to obtain a BN inner cladding with a target thickness of 1 to 10 μm. Step 5: After the BN inner cladding deposition is completed, cool it to room temperature and place the reacted sapphire optical fiber into a SiC deposition furnace; Preparation of SiC outer cladding: Step 6: After the temperature in the SiC deposition furnace is raised, a SiC cladding gaseous precursor is introduced; The temperature of the SiC deposition furnace is raised to 900-1100°C. After the temperature in the SiC deposition furnace is stabilized, a SiC cladding gaseous precursor is introduced into the SiC deposition furnace. The gaseous precursors in the SiC deposition furnace include H2, argon and MTS. The temperature of the methyltrichlorosilane MTS oil bath is raised to 30-35°C. H2 is introduced into the MTS oil bath by a bubbling method. After the H2 is introduced, the gaseous trichloromethylsilane is brought out into the reaction chamber. Argon is introduced into the reaction chamber at the same time for dilution. The gaseous precursor in the SiC deposition furnace is decomposed to generate SiC on the surface of the sapphire optical fiber / BN, and a SiC outer cladding with a target thickness of 1 to 10 μm is obtained. Step 7: After the deposition is completed, the introduction of the reaction gas source is stopped, and the deposition furnace is cooled to room temperature to obtain sapphire optical fiber / BN / SiC.

2. The method for preparing a double-cladding sapphire optical fiber capable of withstanding high temperatures and serving for a long time in air according to claim 1, characterized in that: In step 4, the H2 flow rate is 50-200 ml / min; the BCl3 flow rate is 10-100 ml / min; the NH3 flow rate is 30-200 ml / min; and the argon flow rate is 50-200 ml / min.

3. The method for preparing a double-cladding sapphire optical fiber capable of withstanding high temperatures and long-term service in air according to claim 1, characterized in that: In step 6, the H2 flow rate is 20-2000 ml / min; the argon flow rate is 10-2000 ml / min.

4. The method for preparing a double-cladding sapphire optical fiber capable of withstanding high temperatures and long-term service in air according to claim 1, characterized in that: In step 6, the temperature is maintained for 1-100 hours.

Citation Information

Patent Citations

  • Method for manufacturing ceramic matrix composite boron nitride interface coating

    CN105463403A

  • Chemical vapor deposition preparation method for sapphire optical fiber BN total reflection coating

    CN109704599A

  • Preparation method of diamond-SiC composite substrate with adjustable thermal conductivity

    CN116121725A

  • Sapphire fiber grating high-temperature sensor

    CN210774419U

  • Film deposition apparatus

    US20120006263A1